Management of “Bilateral Foot Drop” through Ayurveda- A Case Study - Nasheeda , P; Anand, P K V; Rahul (International Research Journal of Ayurveda & Yoga, 2023)
Foot drop can be caused by paralysis of pretibial and peroneal muscles with resultant inabilityto dorsi flex the foot. The most common causes of foot drop are L5 radiculopathy and peronealnerve injury. Here a case of 74 year old man presented with weakness of both lower limbs andnumbness of both sole of foot since 10 years brought to OPD. He was provisionally diagnosedas a case of peroneal mono neuropathy, later diagnosed as a case of Bilateral Foot Drop. As per ayurvedic classics, we have correlated this condition as Pangu, a condition which is causeby vitiation of Vata. Hence the line of treatment we have adopted was Vatavyadhi Chikitsa, which comprises of Amapachana as well as Balya and Brumhana Chikitsa along with Samanoushadhi. The outcome was significant, that the patient was able to walk more confidently without the fear of falling.